FIST's postgraduates during the 6th UMP convocation - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Chin, Mei Lee; Siti Aisah, Harun; Norhayati, Nordin; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras; Nurul Nadia, Abd Razak (Penerbit UMP, 2011)
OCT 10, GAMBANG : UMP's 6th Convocation was held on 1st October 2.011 at UMP's Sports Complex which witnessed 1 ,2.90 graduates receiving their doctoral, master and bachelor degrees and diplomas.